Magnetic Adsorbent Fe3O4/ZnO/LC for the Removal of Tetracycline and Congo Red from Aqueous Solution - Anjiu Zhao; Qi Tang; Yuanlong Chen; Chongpeng Qiu; Xingyan Huang (Molecules, 2023)
Zeolitic imidazolate frameworks (ZIFs) can be used as an adsorbent to efficiently adsorb organic pollutants. However, ZIF nanoparticles are easy to form aggregates, hampering the effective and practical application in practical adsorption. In this study, the ZIF-8 was successfully loaded onto lignocellulose (LC) to further produce ZnO/LC by in situ growth method and hydrothermal treatment, and then Fe3O4 nanoparticles (Fe3O4 NPs) were loaded onto ZnO/LC to prepare magnetic Fe3O4/ZnO/LC adsorbent for removing tetracycline (TC) and congo red (CR) pollutants from aqueous solution. The adsorption properties of the adsorbent were systematically analyzed for different conditions, such as adsorbent dosage, solution pH, contact time, temperature and initial concentration. The experimental data were fitted using adsorption kinetic and isotherm models. The results showed that the pseudo-second-order model and Sips model were well fitted to the adsorption kinetic and adsorption isotherm, respectively. The adsorption capacities of TC and CR reached the maximum value of 383.4 mg/g and 409.1 mg/g in experimental conditions. The mechanism of the removal mainly includes electrostatic interaction, hydrogen bonding and π-π stacking. This novel adsorbent could be rapidly separated from the aqueous solution, suggesting its high potential to remove pollutants in wastewater.